Imaging of pain using positron emission tomography - Zhou, Yu‐Peng; Zhang, Lauren L.; Sun, Yang; Brugarolas, Pedro (iRadiology (Online), 2024)
Positron emission tomography (PET) is a noninvasive molecular imaging technique that utilizes biologically active radiolabeled compounds to image biochemical processes. As such, PET can provide important pathophysiological information associated with pain of different etiologies. Consequently, the information obtained using PET often combined with magnetic resonance imaging or computed tomography can provide useful information for diagnosing and monitoring changes associated with pain. This review covers the most important PET tracers that have been used to image pain including tracers for fundamental biological processes such as glucose metabolism and cerebral blood flow, to receptor‐specific tracers such as ion channels and neurotransmitters. For each tracer, we describe the structure and radiochemical synthesis of the tracer followed by a brief summary of the available preclinical and clinical studies. By providing a summary of the PET tracers that have been employed for PET imaging of pain, this review aims to serve as a reference for preclinical, translational, and clinical investigators interested in molecular imaging of pain. Finally, the review ends with an outlook of the needs and opportunities in this area. In this review, the positron emission tomography (PET) tracers that are used in pain imaging are summarized. These PET tracers can be utilized to visualize glucose metabolism, cerebral blood flow, bone metabolic activity, neurotransmitter receptor occupancy, ion channel expression level, enzyme activity, chaperone protein expression level, neuroinflammation, etc., under various painful conditions. PET imaging provides a better understanding and identification of the pain mechanism, which are the keys to precise and personalized pain treatment and management.